Creación del departamento de talento humano bajo el modelo de gestión por competencias para la empresa Agripalban banano año 2015 - Orbe Almeida, Lourdes Cecilia (2016)
This research work it performed as a contribution to the company Agripalban Banana, which emphasizes the importance of the creation of the department of human talent so they can better manage staff, whose principal objective is to create the department human talent, under the model of competency management for company employees Agripalban Banana, which is run by his manager who agreed to this project, it has included the level of what the design of the new department, which without certainly bring benefits to all staff, and improve human talent management company. To collect the necessary information for obtaining data interview were made to the manager and employee surveys respectively, the same as tabulated in the tool EXCEL, in which were determined after the investigation existing shortcomings such as; the lack of a department of human talent and identify the organizational structure of the department, which are to be implemented in the company. Recommendations given to the company to finalize how important it is to create a department of human talent in order to improve welfare, business productivity and employee in the company Agripalban Banana.